Manajemen Kebersihan Menstruasi pada Siswi SMA IT Nurul Ilmi di Kota Jambi - Ajeng Galuh Wuryandari; Lia Artika Sari; Netti Herawati (Jurnal Abdimas Kesehatan (JAK), 2021)
Everyday, an estimated 300 million women and girls menstruate. The main problem for adolescents during menstruation is the lack of knowledge about menstrual hygiene management (MHM). During menstruation, women should really be able to keep the reproductive organs extra clean, especially the vaginal part, because if they are not kept clean, it will cause excess microorganisms and can interfere with reproductive function. The purpose of this community service is to identify the knowledge and understanding of students about menstrual hygiene management. This activity was attended by as many as 150 students. The method used in this community service through several stages, including compiling an activity plan, coordinating and advocating with the school, the second stage, namely implementation by providing material on online menstrual hygiene management with ZOOM teleconferencing media, evaluating activities through Google Form. This community service was carried out at SMA IT Nurul Ilmi. The need for comprehensive reproductive health assistance and education related to menstrual hygiene management for young girls